ERWIN SMITH’S EMOTIONAL INTELLIGENCE IN SHINGEKI NO KYOJIN MANGA: KECERDASAN EMOSIONAL TOKOH ERWIN SMITH DALAM MANGA SHINGEKI NO KYOJIN - Bella Yulia; Tienn Immerry; Femmy Dahlan; Irma Irma (Jurnal Kata, 2023)
This research aims to reveal Erwin Smith’s emotional intelligence seen in Shingeki no Kyojin manga. Erwin, the Commander of the Scout Legion, has the ambition and goodwill to protect the human race from the attack of Titans, giant monsters. Golemen’s theory of emotional intelligence was applied to examine Erwin’s ability to control his emotions and his understanding of the emotions of others. A qualitative method was utilized in this research. The data on Erwin’s emotional intelligence were obtained through observation and note-taking techniques. The results show Erwin’s dominant personality traits (ambitious, enthusiastic, and self-confident) contributed to his achievement on all components of emotional intelligence: self-awareness, self-regulation, motivation, empathy, and social skills. Erwin’s emotional intelligence is well-accomplished due to those dominant personality traits, meanwhile his patience and kindness act as the controller and balancer.